Περιβαλλοντική πληροφορία και κυπριακή πραγματικότητα : εφαρμογή της συνθήκης του AARHUS - Άχχας, Νικόλας (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος,Τεχνολογικό πανεπιστήμιο Κύπρου, 2013)
In the information age we live in, environmental information is of great socio‐economic and political significance. The rapid developments in the field of Information Technology and Communication (ICT) together with people’s need to be aware of the environmental dangers that lurk, gave governments the opportunity to gain citizens’ confidence, providing transparency in the information held by the government concerning the environment. These developments have resulted in the emergence of the recent European Directive 2003/4/EC on public access to environmental information, replacing the previous Directive 90/313/EEC. Therefore, the aim of the thesis that follows is to investigate the accessibility of the public on environmental information issues that are found in the public service departments of our country and to identify any difficulties. What follows is an attempt to come up with proposals concerning the management of environmental information in Cyprus, as well as ways of public consultation, the evaluation of the existing system and the provision of suggestions in order to facilitate the process of demanding‐supplying environmental information. The thesis’ recommendations also include the promotion of environmental education government programs and training that has to do with the use of computers. Main results ‐ conclusions from the above are the factors that have contributed to today's access to environmental information, which seems to be the development of ICT, the citizens’ need for social security and transparency policy implemented by governments.
Keywords: Environmental information; Technology and communication